Preparation and Characterization of Ceramic Membrane Composition Variations in Pome Waste Treatment - Isnandar Yunanto; Silviyati, Idha; Elvani, Lian; Trisnaliani, Lety (Aptisi Transactions On Technopreneurship (ATT), 2022)
Palm Oil Mill Effluent (POME) is waste generated by the palm oil industry consisting of solid, liquid and gaseous wastes. POME is decomposed in sewage ponds and allowed to decompose naturally. The residual waste generated by this industry is non-toxic but has high polluting power. To overcome this, it is necessary to treat waste by making ceramic membranes. The composition materials needed are clay, zeolite, sodium carbonate and boric acid. The manufacturing method is through the printing and combustion stages at a temperature of 900oC. The results showed that there was an effect of compositional variations on the quality of the final product, namely TSS rejection % 93.355 with a flux value of 0.2474 (L/m2min). From the parameter values obtained, it proves that the ceramic membrane is able to process POME with satisfactory effective results. The quality standard of palm oil liquid waste is in accordance with South Sumatera governor regulation number 8 of 2012 concerning quality standard of liquid waste for industrial, hotel, hospital, domestic and coal mining activities